Yu-Ping-Feng Formula Ameliorates Alveolar-Capillary Barrier Injury Induced by Exhausted-Exercise via Regulation of Cytoskeleton - Wang, Di; Li, Quan; Pan, Chun-Shui; Yan, Li; Sun, Kai; Wang, Xiao-Yi; Anwaier, Gulinigaer; Liao, Qian-Zan; Xie, Ting-Ting; Fan, Jing-Yu; Huo, Xin-Mei; Wang, Yuan; et al. (Frontiers in Pharmacology, 2022)
Background: Yu-ping-feng powder (YPF) is a compound traditional Chinese medicine extensively used in China for respiratory diseases. However, the role of YPF in alveolar-capillary barrier dysfunction remains unknown. This study aimed to explore the effect and potential mechanism of YPF on alveolar-capillary barrier injury induced by exhausted exercise. Methods: Male Sprague–Dawley rats were used to establish an exhausted-exercise model by using a motorized rodent treadmill. YPF at doses of 2.18 g/kg was administrated by gavage before exercise training for 10 consecutive days. Food intake-weight/body weight, blood gas analysis, lung water percent content, BALF protein concentration, morphological observation, quantitative proteomics, real-time PCR, and Western blot were performed. A rat pulmonary microvascular endothelial cell line (PMVEC) subjected to hypoxia was applied for assessing the related mechanism. Results: YPF attenuated the decrease of food intake weight/body weight, improved lung swelling and hemorrhage, alleviated the increase of lung water percent content and BALF protein concentration, and inhibited the impairment of lung morphology. In addition, YPF increased the expression of claudin 3, claudin 18, occludin, VE-cadherin, and β-catenin, attenuated the epithelial and endothelial hyperpermeability in vivo and/or in vitro, and the stress fiber formation in PMVECs after hypoxia. Quantitative proteomics discovered that the effect of YPF implicated the Siah2-ubiquitin-proteasomal pathway, Gng12-PAK1-MLCK, and RhoA/ROCK, which was further confirmed by Western blot. Data are available via ProteomeXchange with identifier PXD032737. Conclusion: YPF ameliorated alveolar-capillary barrier injury induced by exhausted exercise, which is accounted for at least partly by the regulation of cytoskeleton.